PENOLAKAN PERMOHONAN PEMBATALAN AKTA HIBAH KARENA ADANYA CACAT HUKUM (Studi Komparasi Putusan Pengadilan Negeri Surakarta No. 111/Pdt.G/2001/PN.Ska., Putusan PengadilanTinggi Semarang No. 370/Pdt/2003/PT.Smg., dan Putusan Mahkamah Agung No. 2590 K/Pdt/2004) - , IKA DYAH WIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed at analyzing the bases of consideration of the Verdict of Semarang Appeal Court No. 370/Pdt/2003/PT.Smg, in finding elements of legal defect so that it accepted the request of bequest deed annulment and analyzing the consideration of the Verdict of Surakarta District Court No. 111/Pdt.G/2001/PN.Ska, and the Verdict of the Supreme Court No. 2590 K/Pdt/2004 which rejected the request of bequest deed annulment. This research is a juridical normative research, employing secondary data through library research grounded on primary law materials, secondary law materials and tertiary law materials. Data were collected through documentation method using documentary study instrument. The research data were analyzed using qualitative analysis method. The result of research and discussion indicate that the judge of Semarang Appeal Court annulled the bequest deed because the judge found an oversight element and according to the judgeâs consideration the bequest agreement had violated the agreement of land management and the agreement of appointment and management of Gas Station. while the judge of Surakarta District Court did not annul the bequest deed because the plaintiff in the trial filed written evidences which were only in the form of copied agreement documents without any legalization, were not affixed with stamp, and not accompanied with the original documents in front of the panels of judges. The judge of the Supreme Court rejected the request of the bequest deed annulment because there was no any dispute between the parties when the deed was made. Based on the result of research and discussion, it can be concluded that the judge of Semarang Appeal Court did not mention clearly the oversight. In regard to the judgeâs consideration that the Bequest Agreement had violated the Land Management Agreement, this had been refuted with written evidences from the Regional Government of Surakarta. The judge of Surakarta District Court did not consider other evidences, namely photocopy of the deed from the defendants and witness of the defendants. The verdict of the Supreme rejected the annulment of bequest deed because there was no any dispute between the parties. The bequest was done when the parties were still in wedlock and the bequest agreement was not disputed by the Regional Government of Surakarta and PERTAMINA. Therefore, it is suggested that the judge in giving consideration should more careful and precise while giving legal bases and while giving the verdict based on the consideration so that there is a correlation between consideration and the verdict. If someone wishes to make a bequest agreement, he/she had better know the consequences of what they will do so that in the future there will be no annulment of bequest which will be disadvantageous for themselves and the parties related in the bequest agreement.